Penerapan Model Direct Instruction dengan Metode Jarimatika untuk Meningkatkan Hasil Belajar Pada Materi Pecahan di Kelas III Madrasah Ibtidaiyah - Jarmita, Nida; Hayati, Zikra; Meilita, Fauza (Pencerah, 2024)
Multiplication is a fundamental concept that students at the Primary School level must master, as it serves as a foundation for advanced Mathematical operations. However, many early-grade Madrasah students still struggle with multiplication, particularly with numbers ranging from six to ten. One effective instructional method to facilitate students' understanding and execution of multiplication is the jarimatika method. This method uses fingers as counting tools, making it easier for students to grasp multiplication concepts. This study aims to examine the improvement in students' learning outcomes through the implementation of the jarimatika method in teaching multiplication to third-grade students at MIS Lamgugob Banda Aceh. The research employs a Classroom Action Research (CAR) approach, with a total of 40 third-grade students as participants. Data were collected using test instruments and observation sheets and analyzed using percentage formulas to assess learning improvements. The findings reveal that the implementation of the jarimatika method significantly improved students' learning outcomes across the cycles. In Cycle I, 62.5% of students achieved the minimum mastery criterion (MMC), increasing to 80% in Cycle II and 90% in Cycle III. These results indicate that the jarimatika method is effective in enhancing students’ understanding of multiplication concepts and improving their overall learning outcomes. This study recommends the adoption of the jarimatika method as an alternative instructional strategy for teaching mathematics at the Primary School level.